2013
DOI: 10.1182/blood-2012-08-452995
|View full text |Cite
|
Sign up to set email alerts
|

IL-21–stimulated human plasmacytoid dendritic cells secrete granzyme B, which impairs their capacity to induce T-cell proliferation

Abstract: • pDCs functionally express the IL-21 receptor and produce granzyme B in response to IL-21.• IL-21-induced granzyme B in pDC impairs pDC's capacity to induce T-cell proliferation.Plasmacytoid dendritic cells (pDCs) play a crucial role during innate immunity by secreting bulk amounts of type I interferons (IFNs) in response to Toll-like receptor (TLR)-mediated pathogen recognition. In addition, pDCs can also contribute to adaptive immunity by activation of antigen-specific T cells. Furthermore, it is well estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
3
29
0
1
Order By: Relevance
“…2). In addition, we and others have shown that pDCs secrete high amounts of GrB when exposed to IL-21 [239,240], a Th17-cytokine that is strongly expressed in lesional skin of LE patients [241]. Because pDCs do not express perforin [242], a cytotoxic role for pDC-derived GrB remained uncertain.…”
Section: Other Functions Of Dcs In Autoimmune Diseasesmentioning
confidence: 95%
“…2). In addition, we and others have shown that pDCs secrete high amounts of GrB when exposed to IL-21 [239,240], a Th17-cytokine that is strongly expressed in lesional skin of LE patients [241]. Because pDCs do not express perforin [242], a cytotoxic role for pDC-derived GrB remained uncertain.…”
Section: Other Functions Of Dcs In Autoimmune Diseasesmentioning
confidence: 95%
“…IL-21 seems to be important for granzyme expression in different cell types, such as B cells (Hagn et al, 2009) and plasmacytoid dendritic cells (Karrich et al, 2013). The expression of granzymes in some cells is controversial: for example in neutrophils reviewed in (Susanto et al, 2012) or human polymorphonuclear leukocytes .…”
Section: Expression Of Granzymesmentioning
confidence: 99%
“…In mDCs, no constitutive GrB protein expression is reported, but GrB and perforin protein expression can be induced by treatment with TLR7 and TLR8 agonists (59). In contrast, TLR7 and TLR9 agonists inhibit GrB protein expression in pDCs (57)(58)(59)(60).…”
Section: Unresolved Questionsmentioning
confidence: 99%
“…There is ample evidence that both human mye-loid dendritic cells (mDCs) and human plasmacytoid DCs (pDCs) express GrB (56)(57)(58)(59)(60). Constitutive mRNA and protein expression has been found in pDCs (57,60), whereas IL-3, IL-10, and IL-21 upregulate GrB mRNA and protein expression in these cells (57,58,60). In mDCs, no constitutive GrB protein expression is reported, but GrB and perforin protein expression can be induced by treatment with TLR7 and TLR8 agonists (59).…”
Section: Unresolved Questionsmentioning
confidence: 99%